A prospective, randomized trial of intravenous hydroxocobalamin versus noradrenaline or saline for treatment of lipopolysaccharide‐induced hypotension in a swine model. (19th February 2019) - Bebarta, Vikhyat S.; Garrett, Normalynn; Maddry, Joseph K.; Arana, Allyson; Boudreau, Susan; Castaneda, Maria; Dixon, Patricia; Tanen, David A.
Summary: Early, non‐clinical studies support the use of hydroxocobalamin to treat sepsis‐induced hypotension, but there is no translational, large animal model. The objective of this study was to compare survival in a sepsis model where large swine had endotoxaemia induced with lipopolysaccharide (LPS) and were treated with intravenous hydroxocobalamin (HOC), noradrenaline (NA), or saline. Thirty swine (45–55 kg) were anaesthetized, intubated, and instrumented with continuous femoral and pulmonary artery pressure monitoring. Hypotension, predefined as 50% of baseline, was induced with LPS. Animals then received HOC, NA, or saline and monitored for 3 hours. The main outcome was survival to the conclusion of the study. Using a power of 80% and an alpha of 0.05, 10 animals were used per group. Secondary outcomes included: mean arterial pressure (MAP), systemic vascular resistance (SVR) and cardiac output (CO) along with several markers of sepsis. No differences were detected between groups at baseline or after hypotension. The survival distributions of the three groups were significantly different with more HOC animals surviving (10/10) compared with NA (8/10) or Saline (5/10) (log‐rank P < 0.03). MAP was found to be higher in both the HOC and NA groups and HOC achieved the highest SVR. In this large animal, translational study of an endotoxaemic model of sepsis, hydroxocobalamin improved survival when compared with saline.